2014
DOI: 10.1007/s00439-014-1471-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms associated with rubella virus-specific cellular immunity following MMR vaccination

Abstract: Rubella virus causes a relatively benign disease in most cases, although infection during pregnancy can result in serious birth defects. An effective vaccine has been available since the early 1970s and outbreaks typically do not occur among highly vaccinated (≥2 doses) populations. Nevertheless, considerable inter-individual variation in immune response to rubella immunization does exist, with single dose seroconversion rates ~95%. Understanding the mechanisms behind this variability may provide important ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Our finding is similar to Feng’s observation of RV‐IgM prevalence in 2009 . Although the advent of vaccine has decreased the incidence of RV infection and CRS dramatically, women are advised not to become RV‐vaccinated during pregnancy . The limitation of this study is that the data were collected from a 12‐month period; cumulative observation for years might provide a better understanding about the seasonal influence on TORCH infections …”
Section: Discussionsupporting
confidence: 86%
“…Our finding is similar to Feng’s observation of RV‐IgM prevalence in 2009 . Although the advent of vaccine has decreased the incidence of RV infection and CRS dramatically, women are advised not to become RV‐vaccinated during pregnancy . The limitation of this study is that the data were collected from a 12‐month period; cumulative observation for years might provide a better understanding about the seasonal influence on TORCH infections …”
Section: Discussionsupporting
confidence: 86%
“…BTN3A3 may act as one of the inhibitors of co-stimulation for T lymphocyte priming, similar to CTLA-4 [38]. It also found that SNPs near the butyrophilin genes ( BTN3A3/BTN2A1 ) are associated with variations in IFN-γ secretion [39]. As for FLOT1 (flotillin-1), another gene verified by our ELISA test, its important roles in promoting tumorigenesis and progression of several cancers like non-small cell lung cancer, breast cancer and hepatocellular carcinoma have been recently reported [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicating that specific risk factors exist have been provided in the literature, including the role of age, sex, and SNPs [3,5,16,39,44,45,47].…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have been reported on this topic, including significant evidence about the role of several SNPs in cytokines production following vaccinations [44][45][46][47][48][49][50].…”
Section: The Molecular Mechanismmentioning
confidence: 98%
See 1 more Smart Citation